Students’ Discipline Problems and Classroom Management Strategies to Cope with the Problems: Teachers’ Perspective - Maqsood Ahmed, Ishtiaq Hussain (JCTE, 2023)
The main purpose of this study was to get an insight into the perceptions of teachers about student discipline problems and classroom management strategies adopted by them. Data were collected from 86 secondary school teachers, teaching in various Federal Government Institutions of Islamabad, through the administration of the researchers-made questionnaire. Additionally, semi-structured interviews from 6 participants were also conducted to get in depth views of the teachers about the discipline issues of students and their management strategies in the context of classroom and school. The focus of the study was on characteristics of students creating problems in the classroom, the most frequently occurring and major causes of discipline problems, and classroom management strategies used by teachers to improve discipline. Teachers' opposed the practices of traditional punitive strategies in classrooms; they suggested the use of soft disciplinary skills in case of students' unwanted behaviour.